Selective 40S footprinting reveals cap-tethered ribosome scanning in human cells - Bohlen, Jonathan; Fenzl, Kai; Kramer, Günter; Bukau, Bernd; Teleman, Aurelio A. (Molecular cell, 2020)
Translation regulation occurs largely during the initiation phase. Here, we develop selective 40S footprinting to visualize initiating 40S ribosomes on endogenous mRNAs in vivo. This reveals the positions on mRNAs where initiation factors join the ribosome to act and where they leave. We discover that in most human cells, most scanning ribosomes remain attached to the 5′ cap. Consequently, only one ribosome scans a 5′ UTR at a time, and 5′ UTR length affects translation efficiency. We discover that eukaryotic initiation factor 3B (eIF3B,) eIF4G1, and eIF4E remain bound to 80S ribosomes as they begin translating, with a decay half-length of ∼12 codons. Hence, ribosomes retain these initiation factors while translating short upstream open reading frames (uORFs), providing an explanation for how ribosomes can reinitiate translation after uORFs in humans. This method will be of use for studying translation initiation mechanisms in vivo.
Gesehen am 12.10.2020